MANAJEMEN PENDIDIKAN KARAKTER DI SMA IT ANNAS 1 MANDAI MAROS - Wahyu Sandy Setiawan Basri; Kamaruddin Hasan; Farida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Character education is an important aspect of the educational process that aims to develop students who possess noble character, are responsible, disciplined, and caring toward their social environment. This study aims to analyze the implementation of character education through the development of school culture at SMA IT Annas 1 Mandai Maros. The study employs a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving the principal, vice principal, teachers, and students. Data analysis utilized the Miles and Huberman interactive model, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that character education is implemented through the school culture, which encompasses religious practices, teacher role modeling, the enforcement of discipline, a culture of literacy, environmental awareness, and extracurricular activities. The character values developed include religiosity, discipline, creativity, a spirit of nationalism, a love of reading, and environmental awareness. Supporting factors include teacher competence, school leadership, adequate facilities and infrastructure, and collaboration among the entire school community. Hindering factors include differences in student character, limited instructional time, and the influence of the environment outside of school. This study concludes that school culture serves as an effective medium for developing students’ character in a holistic and sustainable manner.